Synthesis of potentially biobased copolyesters based on adipic acid and butanediols: Kinetic study between 1, 4- and 2, 3-butanediol and their influence on crystallization and thermal properties. (2nd September 2016) - Debuissy, Thibaud; Pollet, Eric; Avérous, Luc
Abstract: Different potentially biobased copolyesters with specific macromolecular architectures are successfully synthesized from renewables diols and diacids, and characterized. The first part focuses on the study of the esterification kinetic of two equimolar systems, 1, 4-butanediol (1, 4-BDO)/adipic acid (AA) and 2, 3-butanediol (2, 3-BDO)/AA, with and without titanium isopropoxide (TTIP) as catalyst. The influence of the type of diol (primary vs. secondary hydroxyl groups) and the temperature is also investigated. The esterification rate with 2, 3-BDO is slower than with 1, 4-BDO leading to higher activation energy. In the second part, poly(1, 4-butylene adipate) (PBA) and poly(2, 3-butylene adipate) (PB'A) aliphatic polyesters and the corresponding copolyester [poly(1, 4-butylene adipate-co-2, 3-butylene adipate) (PBB'A)] are synthesized by transesterification in bulk using TTIP. According to our knowledge, the synthesis of PBB'A is reported here for the first time. All synthesized copolymers are characterized by NMR, SEC, FTIR, WAXS, MALDI-TOF, DSC, TGA and specific optical rotation. PBA with a mass-average molar mass around 60, 000 g/mol is obtained, whereas molar mass of PB'A and PBB'A are significantly lower. The 2, 3-BDO molar content in copolyesters is lower than the initial molar feed content. A linear evolution is observed between 2, 3-BDO content and specific optical rotation of the polyesters allowing to use this relation as an additional method to determine PBB'A composition. PBA shows a semi-crystalline behavior, whereas PB'A is amorphous. An increase of the 2, 3-BDO content in the copolyester raises the glass transition temperature and reduces the crystallinity. All polyesters exhibit a good thermal stability, exceeding 280 °C, with a maximum rate of degradation around 380 °C. Graphical abstract: Highlights: Synthesis of a copolyester based on 2, 3-butanediol with tunable properties. Esterification kinetic study between 1, 4-butanediol and 2, 3-butanediol with adipic acid. Lower molar mass obtained for copolyesters containing 2, 3-butanediol. Optical active polymers with excellent thermal stability until 250 °C. From semi-crystalline to fully amorphous copolyesters for increasing 2, 3-BDO contents.